Contrast sensitivity function in patients with macular disease and good visual acuity. Issue 6 (3rd February 2021) - Wai, Karen M; Vingopoulos, Filippos; Garg, Itika; Kasetty, Megan; Silverman, Rebecca F; Katz, Raviv; Laíns, Inês; Miller, Joan W; Husain, Deeba; Vavvas, Demetrios G; Kim, Leo A; Miller, John B
Abstract : Introduction: Contrast sensitivity function (CSF) may better estimate a patient's visual function compared with visual acuity (VA). Our study evaluates the quick CSF (qCSF) method to measure visual function in eyes with macular disease and good letter acuity. Methods: Patients with maculopathies (retinal vein occlusion, macula-off retinal detachment, dry age-related macular degeneration and wet age-related macular degeneration) and good letter acuity (VA ≥20/30) were included. The qCSF method uses an intelligent algorithm to measure CSF across multiple spatial frequencies. All maculopathy eyes combined and individual macular disease groups were compared with healthy control eyes. Main outcomes included area under the log CSF (AULCSF) and six CS thresholds ranging from 1 cycle per degree (cpd) to 18 cpd. Results: 151 eyes with maculopathy and 93 control eyes with VA ≥20/30 were included. The presence of a maculopathy was associated with significant reduction in AULCSF (β: −0.174; p<0.001) and CS thresholds at all spatial frequencies except for 18 cpd (β: −0.094 to −0.200 log CS, all p<0.01) compared with controls. Reductions in CS thresholds were most notable at low and intermediate spatial frequencies (1.5 cpd, 3 cpd and 6 cpd). Conclusion: CSF measured with the qCSF active learning method was found to be significantly reduced in eyes affected by macular disease despite good VA compared with healthy control eyes. The qCSF method is a promising clinical tool to quantify subtle visual deficits that may otherwise go unrecognised by current testing methods.